1998
DOI: 10.1136/jech.52.9.564
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of joint replacement surgery for patients with osteoarthritis: prospective evaluation using independent assessments in Scotland

Abstract: Study objectives-To determine extent of change in psychological, functional, and social health after knee and hip joint replacement surgery using independent assessments. Design-Patients were recruited before surgery and interviewed preoperatively, three months after surgery, and nine months after surgery. Interviews were conducted in the patients' own homes. Setting-Two orthopaedic surgery units in Scotland. Participants-A consecutive sample of 107 patients with osteoarthritis having primary replacement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 13 publications
2
26
1
Order By: Relevance
“…5 However, loss of weight in obese patients awaiting surgery is difficult, partly because the symptoms limit their ability to exercise, and they often believe that joint replacement is crucial for weight loss. Improvements of function and quality of life (QoL) occur within three months of TKR, [6][7][8][9] and thus the perceived barrier to weight loss should be removed at this time. There is, however, little information on the impact of TKR on subsequent weight loss, although it has been suggested that this may not occur after TKR.…”
mentioning
confidence: 99%
“…5 However, loss of weight in obese patients awaiting surgery is difficult, partly because the symptoms limit their ability to exercise, and they often believe that joint replacement is crucial for weight loss. Improvements of function and quality of life (QoL) occur within three months of TKR, [6][7][8][9] and thus the perceived barrier to weight loss should be removed at this time. There is, however, little information on the impact of TKR on subsequent weight loss, although it has been suggested that this may not occur after TKR.…”
mentioning
confidence: 99%
“…The nurses' perception may have been influenced by the fact that the majority of patients commence full weight bearing on the operated leg by the second post-operative day (Lucas, 2004). Therefore, in the absence of collaborative problems improvement in the individual's ambulatory, recreational and occupational function can be anticipated from an early stage (Orbell et al, 1998). Young et al (1999) contended that the concept of rehabilitation must reflect not just the function of a body part alone but of the whole person, set in the context of their personal circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in function and quality of life occur within three months of TKR so the perceived obstacle to weight loss should be lifted by this time. [72][73][74][75] A prospective, continuous study of 529 patients who underwent primary TKR was recently reported by Dowsey et al 76 They aimed to investigate weight change and the functional and clinical outcome in non-obese and obese groups 12 months post-operatively. After 12 months, 40 (12.6%) of the obese patients had achieved a clinically significant weight loss of 5%, but 107 (21%) had actually gained weight.…”
Section: Treatmentmentioning
confidence: 99%